FORMATION OF VALUE CHAINS FOR GREEN HYDROGEN - Svitlana O. Fedulova; Oleksandr A. Pivovarov; Andrii Ya. Kalynovskyi (Academy Review)
The world is entering an unprecedented period when our energy systems will begin to radically change. The article is devoted to the issue of determining the features of the formation of green hydrogen value chains. The main idea of the study was to identify and describe the potential opportunities for the rapid growth of the global hydrogen economy and the features of value creation for green hydrogen in the specified conditions of the global hydrogen economy. It has been noted that the delay in the development of a systematic and mature hydrogen economy is mainly due to difficult storage conditions and the safety aspect of its transportation. It has been substantiated that the green hydrogen value chain can be divided into the following elements: upstream (production), intermediate (storage and transportation), and downstream (end consumption). Each of these components of the hydrogen value chain needs to address its own technical and socio-economic challenges. The hydrogen production process carries production costs, as it is not a naturally occurring source, making it three times more expensive than fossil fuels. It should also be considered that storage and transportation can still significantly increase the cost of hydrogen as a product. Thus, the storage and transportation of hydrogen reserves present significant challenges. The study analytically proves that, even though hydrogen has almost three times the energy content of transportation fuel, it is still almost three times more expensive to use than other fossil fuels under today’s conditions and prices. At the same time, the article notes that molecular hydrogen is the most optimistic solution for achieving a carbon-neutral energy economy, and it requires scientific intervention for its production, storage, and transportation. Therefore, the production of green hydrogen from renewable energy sources is considered a potential solution to achieving the goal of reducing carbon emissions in industry, promoting the development of renewable energy sources, and ensuring energy security for countries. The study presents potential features of green hydrogen value creation and describes potential ways of using green hydrogen in the economy in the near future. In the near future, we can expect the use of green hydrogen in the form of a patented mixture of hydrogen and natural gas (Nythane); in production as a fuel for industrial processes, helping to reduce dependence on fossil fuels and minimizing carbon emissions (Nythane and synthetic gas, Power-to-X technologies); in production as a raw material for the production of ammonia and fertilizers; as hydrogen fuel cells for cars; as well as in the energy production sector. When renewable energy production is high, excess renewable energy can help electrolysis create more hydrogen in an environmentally friendly way.